Anterior gradient proteins in gastrointestinal cancers: from cell biology to pathophysiology - Boisteau, Emeric; Posseme, Céline; Di Modugno, Federico; Edeline, Julien; Coulouarn, Cédric; Hrstka, Roman; Martisova, Andrea; Delom, Frédéric; Treton, Xavier; Eriksson, Leif A; Chevet, Eric; Lièvre, Astrid; et al. (Oncogene, 2022)
Most of the organs of the digestive tract comprise secretory epithelia that require specialized molecular machines to achieve their functions. As such anterior gradient (AGR) proteins, which comprise AGR1, AGR2, and AGR3, belong to the protein disulfide isomerase family, and are involved in secretory and transmembrane protein biogenesis in the endoplasmic reticulum. They are generally expressed in epithelial cells with high levels in most of the digestive tract epithelia. To date, the vast majority of the reports concern AGR2, which has been shown to exhibit various subcellular localizations and exert pro-oncogenic functions. AGR2 overexpression has recently been associated with a poor prognosis in digestive cancers. AGR2 is also involved in epithelial homeostasis. Its deletion in mice results in severe diffuse gut inflammation, whereas in inflammatory bowel diseases, the secretion of AGR2 in the extracellular milieu participates in the reshaping of the cellular microenvironment. AGR2 thus plays a key role in inflammation and oncogenesis and may represent a therapeutic target of interest. In this review, we summarize the already known roles and mechanisms of action of the AGR family proteins in digestive diseases, their expression in the healthy digestive tract, and in digestive oncology. At last, we discuss the potential diagnostic and therapeutic implications underlying the biology of AGR proteins.
Keywords: Inflammation; onkogenní proteiny; karcinogeneze; Mucoproteins; mukoproteiny; Mice; Tumor Microenvironment; zánět; Oncogene Proteins; nádorové mikroprostředí; gastrointestinální nádory; proteindisulfidisomerasy; Carcinogenesis; Protein Disulfide-Isomerases; Animals; Gastrointestinal Neoplasms; zvířata; myši